IMPLEMENTASI BUDAYA POSITIF DALAM PEMBENTUKAN KARAKTER SISWA SD NEGERI DI KECAMATAN PAGERBARANG KABUPATEN TEGAL - Ali Nur Fauzi; Eko Burhan Purwanto; Tri Mulyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe and analyze the implementation of positive school culture in shaping students’ character at public elementary schools in Pagerbarang District, as well as to identify the supporting and inhibiting factors involved in the process. The research employed a descriptive qualitative method with data collected through interviews, observations, and documentation. The subjects of the study included principals, Islamic Education and Counseling teachers (PAI and BP), classroom teachers, students, and parents from three public elementary schools: SDN Srengseng 01, SDN Kertaharja 01, and SDN Randusari 06. The findings indicate that positive school culture has been comprehensively implemented through various activities such as morning greetings, collective prayers, Qur'an recitation (tadarus), the 3S habit (Smile, Greet, and Say Hello), and a character points system. These initiatives have had a positive impact on shaping students' religious values, courtesy, and discipline. Key supporting factors include teacher role models, active parental involvement, a conducive school environment, and structured school programs. Meanwhile, challenges encountered include student inconsistency in behavior, limited parental support, time and facility constraints, and underdeveloped evaluation systems.The study concludes that consistently and collaboratively implemented positive school culture effectively fosters student character development. Therefore, synergy between teachers, parents, and school management must be continuously strengthened. The findings reinforce the importance of a character education approach based on habituation, role modeling, and multi-stakeholder collaboration in elementary schools.